The Dynamic Volatilities and Correlations between German Stock Market Indices and Commodities: Evidence from Wavelet and MGARCH-DCC Approaches - Abdullah, Ahmad Monir; Abdullah, Maizatulakma; Jaafar, Romlah (Asian Economic and Financial Review, 2022)
This research investigates the possibilities of diversifying Islamic and conventional stock indices in the German stock market with other commodities, such as crude oil, Bitcoin, and gold. The EUR/USD exchange rate was selected as the robustness test. Our assessment, which was established based on the vector error correction model, reveals that crude oil and German conventional stock index returns have a greater impact on the other variables under consideration. Based on the MGARCH-DCC method, our results indicate that Bitcoin has the least correlation with most variables under consideration, which benefits portfolio diversification. Bitcoin has been exceptionally volatile over the last eight years; therefore, investors would benefit more from including EUR/USD or gold in their portfolio than Bitcoin. According to continuous wavelet transforms (CWT) analysis, the holding period between German stock indices and gold should not be shorter than 128 days because the correlation is exceptionally high within that period.